Intertwined metal homeostasis, oxidative and biotic stress responses in the Arabidopsis frd3 mutant. (4th January 2020) - Scheepers, Maxime; Spielmann, Julien; Boulanger, Madeleine; Carnol, Monique; Bosman, Bernard; De Pauw, Edwin; Goormaghtigh, Erik; Motte, Patrick; Hanikenne, Marc
Summary: FRD3 (FERRIC REDUCTASE DEFECTIVE 3) plays a major role in iron (Fe) and zinc (Zn) homeostasis in Arabidopsis. It transports citrate, which enables metal distribution in the plant. An frd3 mutant is dwarf and chlorotic and displays a constitutive Fe‐deficiency response and strongly altered metal distribution in tissues. Here, we have examined the interaction between Fe and Zn homeostasis in an frd3 mutant exposed to varying Zn supply. Detailed phenotyping using transcriptomic, ionomic, histochemical and spectroscopic approaches revealed the full complexity of the frd3 mutant phenotype, which resulted from altered transition metal homeostasis, manganese toxicity, and oxidative and biotic stress responses. The cell wall played a key role in these processes, as a site for Fe and hydrogen peroxide accumulation, and displayed modified structure in the mutant. Finally, we showed that Zn excess interfered with these mechanisms and partially restored root growth of the mutant, without reverting the Fe‐deficiency response. In conclusion, the frd3 mutant molecular phenotype is more complex than previously described and illustrates how the response to metal imbalance depends on multiple signaling pathways. Significance Statement: This study shows that the phenotype of an frd3 ( ferric reductase defective 3 ) mutant not only results from altered iron, zinc and manganese homeostasis networks, but also from their interconnection with oxidative and biotic stress responses. These observations highlight that the response to transition metal homeostasis imbalance in Arabidopsis is intertwined with multiple signaling pathways.